One witch at a time - DeKeyser, Stacy (Margaret K. McElderry Books, 2015)
When Rudi Bauer sets out for town one morning to trade, he never dreams that Susanna Louisa will sell his family's cow--for magic beans, no less! But that's exactly what she does, and the consequences will be disastrous unless Rudi can return the magic beans to their rightful owner, the evil witch of Petz. The journey to Petz is long and hard, but Rudi and Susanna Louisa soon find a shortcut: a magically sprouted beanstalk leads them straight there...and straight into danger because the evil witch of Petz is a terrible giant who has locked away summer and keeps his kingdom a frozen wasteland. In order to defeat him, Rudi is going to need a little magic of his own.